A STUDY OF INCOME AND EXPENDITURE PATTERN OF THE MOYON TRIBE OF MANIPUR - N.Parthar Moyon; Mayanglambam Sarda Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Individuals' and households' income, savings, spending, and investment patterns are intimately linked and offer valuable insights into the financial behaviour of households. Household income comes from a variety of sources but usually consists of earnings, salaries, and money from employment, self-employment etc. Depending on the family size, age, and income level, household expenses can change. Savings are made for a variety of goals, including a home purchase, education, retirement, and emergency funds. It became imperative that households develop a savings habit. Examining the households' spending and income trends is required for this. The Moyon tribe of Manipur is one of the least studied and researched tribal group. The tribe is working to advance and catch up to the other communities. For this reason, a study of the tribe's income and spending patterns becomes crucial.